Efficacy of electrical stimulation combined with ultrasound acupuncture therapy on treatment in patients with intrauterine adhesions: Study protocol for a placebo-controlled, single-blind, single-center, randomized trial. Issue 50 (16th December 2022) - Xu, Tao; Xie, Li; Qin, Xiaoling; Xie, Xueting; Mo, Sien; Jiang, Qiu; Liang, Feng; Zhu, Xuehong; Li, Bin; Lin, Zhong
Abstract : Background: Recurrence of postoperative adhesions is one of the most important factors for poor reproductive outcomes after hysteroscopic surgery, particularly in cases diagnosed with severe intrauterine adhesions (IUAs), where the recurrence rate is significantly higher. This study aims to explore the effectiveness of the electrical muscle stimulation combined with ultrasound acupuncture therapy in preventing the recurrence of IUAs and improving reproductive outcomes after operative hysteroscopy. Methods: This study is a single-center, randomized controlled trial. A total of 210 patients with IUAs will be randomly assigned into 2 groups according to the ratio of 1:1, as the treatment group and the control group. Participants will receive the electrical muscle stimulation combined with ultrasound acupuncture therapy and oral hormone supplementation or receive oral hormone supplementation only. The primary outcome was the clinical response rate. There were 3 menstrual cycles of treatment and 3 menstrual cycles of follow-up in this study. Ethics and Dissemination: This study protocol was approved by the Ethics Committee of the Reproductive Hospital of Guangxi Zhuang Autonomous Region (approval number: KY-LL-2022-06). This trial will be conducted in accordance with the principles of the Declaration of Helsinki as well as Good Clinical Practice. Study results will be disseminated at academic presentations and publications in peer-reviewed journals. Trial Registration: Registry name: Clinical value of electroultrasonic instrument in the treatment of IUAs and changes of related protein expression; Registry number: ChiCTR2200058901; registration date: April 19 th, 2022; http://www.chictr.org.cn/showproj.aspx?proj=166155 .